The effect of dexamethasone on functional pain following Transoral Robotic Surgery: a randomized double blinded clinical trial - Larsen, Mikkel Hjordt Holm; Channir, Hani Ibrahim; Madsen, Anne Kathrine Østergaard; Rubek, Niclas; O’Leary, Padraig; Kjærgaard, Thomas; Kehlet, Henrik; von Buchwald, Christian (Acta oto-laryngologica)
Pain is prevalent after most TransOral Robotic Surgery (TORS) procedures and may limit function i.e. swallowing. Currently, there is limited knowledge regarding optimal pain treatment in TORS. This clinical trial randomized patients to either a high-dose dexamethasone or low-dose dexamethasone treatment in addition to a multimodal basic analgesic protocol. The aim of the trial was to investigate the pain intensity during rest and swallowing using the Visual Analogue Scale (VAS) after TORS lingual tonsillectomy. Secondary outcomes were acceptable food consistency, nausea, vomiting, opioid rescue usage, length of hospitalization, feeding tube placements, readmissions, blood glucose levels and postoperative complications. The trial was conducted between August 2020 and October 2022. Eligible patients were patients scheduled for TORS-L treatment of obstructive sleep apnea syndrome or as part of the diagnostic work-up of head and neck carcinoma of unknown primary. Eighteen patients were and randomized 1:1. There were overall no significant differences between groups in the reported VAS scores during rest or swallowing ( ≥ .05). Overall, there were no differences in the secondary outcomes. There were no differences in the pain intensity in the two treatment groups allocated to a basic multimodal analgesic package and either high-dose dexamethasone or low-dose dexamethasone treatment. The trial is the first RCT to include pain measurement during a procedure-relevant activity, thus creating a platform for future recovery studies.